2021
DOI: 10.1371/journal.pone.0257325
|View full text |Cite
|
Sign up to set email alerts
|

The Imperial Joint Line Congruency Measurement is a valuable tool in total knee arthroplasty

Abstract: Background Preservation of joint line height is an important factor in post-operative function after Total Knee Arthroplasty (TKA). This is the first study investigating the reliability of the novel Imperial Joint Line Congruency Measurement (IJLCM) technique for the assessment of joint line height using plain radiographs. Methods The reliability of two techniques used to measure joint line height on pre-operative and post-operative plain radiographs is presented. 120 patients that underwent TKA from 6 diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The seminal work by Figgie et al demonstrated an average change in joint line of 8.9mm following primary conventional TKA. The measuring technique has subsequently been demonstrated to have relatively poor inter and intra-observer reliability [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The seminal work by Figgie et al demonstrated an average change in joint line of 8.9mm following primary conventional TKA. The measuring technique has subsequently been demonstrated to have relatively poor inter and intra-observer reliability [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the different methods used to measure joint line height in the literature, it is difficult to compare our findings with those of other authors. Previous work has demonstrated the accuracy, precision and reliability of the measurement technique utilised in this study [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, shown significant posterior condylar offset deviation in CMTKA higher than RATKA group but no significant difference in clinical outcome. Correlated to previous study, Ravi Popat et al [16] , report that deviation of posterior condylar offset in RATKA was significantl lower than CMTKA (2.19 mm. vs 4.24 mm.).…”
Section: Discussionsupporting
confidence: 64%
“…Measurement) [16,31] . The difference in joint line height was calculated by postoperative joint line height (mm.)…”
Section: Joint Line Height Was Measured By Ijlcm Technique (Imperial ...mentioning
confidence: 99%